Antihistamine and cationic amphiphilic drugs, old molecules as new tools against the COVID-19?. (March 2021) - Gitahy Falcao Faria, Clara; Weiner, Luisa; Petrignet, Julien; Hingray, Coraline; Ruiz De Pellon Santamaria, Ángel; Villoutreix, Bruno O.; Beaune, Philippe; Leboyer, Marion; Javelot, Hervé
Abstract: Several studies have reported that certain psychoactive drugs could have a protective effect against SARS-CoV-2. Herein, we propose that antihistamines (anti-H1) and cationic amphiphilic drugs (CAD), specifically, have the capacity to disrupt virus entry and replication. In addition, several of these molecules have limited side effects and as such could be promising prophylactic candidates against SARS-CoV-2 infection.